Physics teachers initial education and professional performance: what do future teachers have to say? - Bozelli, Fernanda Cátia [UNESP]; Nardi, Roberto [UNESP] (My University, 2012)
This research deals with the discussion about Physics teachers’ undergraduate education and professional performance related to the knowledge acquired during this initial education. More specifically, we try to answer questions like: How do future teachers evaluate the knowledge acquired during their initial education as in terms of specific knowledge as pedagogical knowledge? What are their formative needs and future expectatives about professional performance and the school teaching environment? Data was constituted from a sample of 26 future high school physics teachers, one semester long, that were taking the supervised curricular training in a undergraduate Physics education program (called Licenciatura in Brazil), in São Paulo State public university. Besides the final report of this training, future teachers were asked to answer a questionnaire aiming to take their conceptions about their initial education program, their formative needs, future professional expectatives and high school teaching environment. According to the future teachers, the program they were about to finish was satisfactory in terms of Physics specific contents; however, about the pedagogical content knowledge and the pedagogical practice, they showed to be unsatisfied and insecure. The majority of the questionnaire responses demonstrated that they feel lack of teaching experience. Moreover, teachers emphasize other factors related to the future professional performance: possible difficulties to deal with students’ indiscipline, schools’ bad physical structure, limited number of Physics classes in high school level, lack of didactical laboratories and also they seem to be frightened that the expertise teachers do not be collaborative with the new ones. In this sense, the research outcomes shows the necessity of discussions about questions involving teachers knowledge, related to either, the Physics conceptual domain and the pedagogical one, since it matters directly to future teachers professional performance. Discussions in this sense can also help evaluation and restructuration of programs designed to initial and continuous teachers’ education.

Este documento se centra en la discusión sobre la formación del profesorado en física bajo el sesgo de la formación docente y las actividades profesionales con respecto a los conocimientos adquiridos durante la formación. Más específicamente intentarmos contestar cuestiones del tipo: ¿Cómo los profesores evalúan a los futuros profesores los conocimientos adquiridos en la formación docente, tanto en el conocimiento específico y la enseñanza? ¿Cuáles son sus necesidades de formación y aspiraciones de los resultados futuros y el contexto profesional de la enseñanza en las escuelas? Los datos fueron registrados con una muestra de 26 de los futuros profesores de física de la escuela secundaria, durante un semestre, durante el desarrollo de actividades extraescolares supervisadas, una licenciatura en física, una universidad pública en el Estado de São Paulo, Brasil. Al final del curso, los estudiantes dieron informe sobre el escenario, que también contenía un breve cuestionario para sondear sus opiniones sobre su formación inicial, las necesidades de formación, los deseos y el contexto futuro de la enseñanza en las escuelas. De acuerdo con las respuestas de los estudiantes, la Licenciatura en Física fue satisfactoria en cuanto a conocimiento de los maestros sobre el contenido específico de la física. Pero en el conocimiento de los contenidos educativos, lo que implica la enseñanza de la práctica pedagógica y el conocimiento, know-how, afirman insatisfacción e inseguridad. En cuanto a la falta de experiencia profesional experiencia en la enseñanza parece muy fuertemente en las respuestas de los estudiantes. Además, otros factores que parecen estar complicando para el ejercicio profesional se los alumnos problemáticos, la estructura física de la escuela, el número de clases de física (tiempo), la falta de laboratorios de enseñanza, la falta de cooperación por parte de los profesores con más experiencia, etc. Por lo tanto, es necesario debate en torno al tema del conocimiento de los maestros con respecto tanto en el ámbito conceptual y pedagógico, porque afectan directamente el desempeño profesional de los futuros maestros, y las discusiones de este tipo pueden ayudar a la evaluación y reestructuración de los cursos y la formación la educación continua de los profesores.
Keywords: Physics teachers’ initial education; Physics teachers’ knowledge; Physics teachers’ professional performance; La formación inicial de profesores de Física; Conocimiento de los maestros; La práctica profesional